Review of soft tissue augmentation in the face - James Newman (Dove Medical Press, 2009)
James NewmanFacial Plastic Surgery, Stanford University Medical Center, Palo Alto, CAFacial Plastic Surgery, Stanford University Medical Center, Palo Alto, CA, USAAbstract: A primary pillar of facial rejuvenation is the replacement of soft tissue atrophy via a variety of augmentation techniques. The techniques can be classified into three categories, skeletal onlay grafts, subcutaneous volumizers, and dermal fillers. While onlay grafts and subcutaneous volumizers have the most persistent results, the emergence of improved dermal fillers in the past 5 years has become increasingly popular. An accurate diagnosis of the level(s) of soft tissue atrophy in the face needs to be made prior to selection of the category or combination of techniques. In the younger patient, the selection of a dermal filler or combination of fillers can be adequate for treatment. A comparison of the composition and characteristics of the available dermal fillers are discussed in detail to assist the clinician in understanding the actual mechanism of soft tissue augmentation. In the more advanced aging face, a combination of the three categories may be necessary to produce optimal results. Just as dermal fillers have become more differentiated to increase their longevity, the non-injectible long-lasting implants are becoming more developed to mimic accurate viscoelastic properties of the facial soft tissues. All three classes of augmentation techniques can provide patients with very satisfactory results as part of overall facial rejuvenation.Keywords: soft tissue, dermal fillers, facial implants, facial augmentation